2019
DOI: 10.1088/1742-6596/1256/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Global Blockage Effects in Wind Farms

Abstract: An experimental study of wind farm blockage has been performed to quantify the velocity decrease that the first row of a wind farm experiences due to the presence of the other turbines downstream. The general perception has been that turbines downstream of the first row are only influenced by the wakes from upstream turbines without any upstream effect. In the present study, an attempt is made to demonstrate the existence of a two‐way coupling between individual turbines and turbines in the wind farm. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
4
13
0
Order By: Relevance
“…These effects induce a power decrease and a stronger induction zone for the first turbine. This result is consistent with the experimental observations done by Segalini and Dahlberg [12], which indicates that the velocity in the first row of a wind farm depends on rows behind.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These effects induce a power decrease and a stronger induction zone for the first turbine. This result is consistent with the experimental observations done by Segalini and Dahlberg [12], which indicates that the velocity in the first row of a wind farm depends on rows behind.…”
supporting
confidence: 92%
“…The impact of this effect increases from edge to center, in concordance with the induction zone of the second row-see Figure 19. Effects of the second row on the first row have been observed experimentally by Segalini and Dahlberg [12]. They reported a velocity decrease in the first row of the wind farm due to the presence of rows behind.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Up to 152 turbines were involved in the present measurement campaign. These were freely rotating two-blade plastic rotors with diameter D = 45 mm, similar to what was already used by Ebenhoch et al (2017) and Segalini & Dahlberg (2020). The hub (located at z hub = 60 mm = 1.33D from the ground) consisted of a tube of 3 mm diameter with friction bearings holding the rotor, while a tower with the same diameter was used to support nacelle and rotor.…”
Section: Turbine Detailsmentioning
confidence: 99%
“…Bleeg [104] suggested employing RANS models in combination with a graph neural network approach to model turbine interaction losses and blockage because traditional wake models tend to ignore blockage effects. Segalini et al [90,105] studied wind farm scale blockage in wind tunnel experiments and showed that the front row of a wind farm is negatively impacted by the presence of downstream turbines such that…”
Section: Introductionmentioning
confidence: 99%